An evalution on the level of passenger satisfaction toward the KTM komuter train services in Kuala Lumpur - Tukis, Arisandra; Zainuddin, Nizamuddin (2012)
The concept of customer satisfaction is important in business field.Striving for customer satisfaction means understanding and anticipating what customer want of the services in the future but do not expect of them (Matzler et al. 1996).Customer satisfaction can be taken as an indicator that either customer will uses that service continuously. That services is indicated as a quality if it success to achieve the customer expectation and needs.This paper is to evaluate the level of passenger satisfaction toward the KTM Komuter train services in term of their punctuality, frequency time, speed, space, comfortable, fare level, cleanliness and safety on the train.With having the KTM Komuter trains, it was give convenience to people especially for people who did not have transport.The research result show that almost the services attributes of KTM komuter trains are at a moderate level.Further improvement need to be taken to improve the services and to increase the level of customer satisfaction.